High-performance r-t-b neodymium-iron-boron magnet and method of manufacturing
Patent Information
- Application Number
- CN202611105667.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]目前配方设计中通过铜、铌、钒、钛、锆、镓等微量元素添加,达到细化晶粒的同时提高晶界相的流动性,从而提高矫顽力,但各微量元素之间的作用耦合关系、微量元素与主相硼元素的搭配以及富Nd相和主相连接的三角区域形成的新相研究较少,尤其是通过晶界扩散后的矫顽力性能的提升量不够明显,在同等重稀土使用量下,矫顽力提升量更优的钕铁硼磁体无论是性能还是成本都具备明显的优势,配方设计与优化后的磁体通过晶界扩散后进一步提高磁体综合性能,使得磁体的矫顽力、剩磁与磁能积均能有所提升,已成为业内诸多一线技术研究人员待解决的重要问题之一
[0016]在本发明内,通过各微量元素之间的作用耦合关系、微量元素与主相硼元素的搭配以及富Nd相和主相连接的三角区域的新相形成,使得基体磁体性能提升,而且,通过晶界扩散后的矫顽力得到提高,从而得到高剩磁高矫顽力的磁体。
Smart Images

Figure CN122889538A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of magnetic materials, and in particular to a high-performance RTB neodymium iron boron magnet and its preparation method. Background Technology
[0002] Sintered NdFeB magnets, currently the highest energy density permanent magnets, have been widely used in new energy vehicles, wind power generation, energy-saving air conditioning and elevators. With the rapid development of new energy vehicles, the high-temperature environment for sintered NdFeB magnets is becoming increasingly stringent. Therefore, they are required to have not only high remanence but also high coercivity.
[0003] With the widespread application of grain boundary diffusion technology, the development of efficient infiltration substrates is key to high remanence and high coercivity magnetic properties, and the formulation design of the substrate is the first factor.
[0004] Currently, the addition of trace elements such as copper, niobium, vanadium, titanium, zirconium, and gallium in formulation design aims to refine grains and improve the fluidity of grain boundary phases, thereby enhancing coercivity. However, there is limited research on the interaction and coupling relationships between trace elements, the combination of trace elements with the main phase boron, and the formation of new phases in the triangular regions connecting the Nd-rich phase and the main phase. In particular, the improvement in coercivity performance after grain boundary diffusion is not significant enough. Under the same amount of heavy rare earth elements, NdFeB magnets, which offer a superior improvement in coercivity, have a clear advantage in both performance and cost. Further improving the overall performance of magnets through grain boundary diffusion after formulation design and optimization, thereby enhancing the coercivity, remanence, and energy product of the magnets, has become one of the important problems to be solved by many leading technical researchers in the industry. Summary of the Invention
[0005] To overcome the above shortcomings, the present invention aims to provide a high-performance RTB NdFeB magnet, which improves the performance of the matrix magnet through the interaction and coupling relationship between trace elements, the combination of trace elements and boron elements in the main phase, and the formation of a new phase in the triangular region connecting the Nd-rich phase and the main phase. Moreover, the coercivity is improved through grain boundary diffusion, thereby obtaining a magnet with high remanence and high coercivity. The present invention also provides a method for preparing a high-performance RTB NdFeB magnet.
[0006] The technical solution of this invention to solve its technical problem is: An RTB sintered NdFeB magnet, comprising, by total mass of all components, the following components: R: greater than or equal to 29.5 wt%, wherein R is a rare earth element, and wherein R contains at least Nd; Cu: 0.25wt%~0.60wt%; Ga: 0.15wt%~0.45wt%; B: 0.96wt%~1.20wt%; Fe: 57.0wt%~67.0wt%; Total amount of Zr, Ti and V: 0.20wt%~0.85wt%; in, The ratio of the total mass of Zr and Ti to the mass of V is (0.4~6):1; The mass ratio of B to the total mass of Zr and Ti is (1.6~12):1.
[0007] As an improvement of the present invention, the content of R is 29.5 wt% ~ 32.5 wt%, and the content of Nd is 20.0 wt% ~ 26.0 wt%. The R also includes Pr and / or heavy rare earth element RH, wherein RH is Tb and / or Dy, and the content of RH is ≤3.0wt%.
[0008] As a further improvement of the present invention, the total amount of Zr, Ti and V is 0.30wt%~0.55wt%; the mass ratio of the total mass of Zr and Ti to the mass of V is (1.5~4):1; wherein, the content of Zr is 0.05wt%~0.35wt%; the content of Ti is 0.05wt%~0.25wt%; and the content of V is 0.10wt%~0.25wt%.
[0009] As a further improvement of the present invention, the content of B is 0.98 wt% ~ 1.10 wt%; The ratio of the mass of B to the total mass of Zr and Ti is (2~8):1; The Cu content is 0.35 wt%~0.55 wt%; The Fe content is 60.0 wt%~65.0 wt%; The magnet also contains Co, and the Co content is ≤1.5wt%.
[0010] As a further improvement of the present invention, the microstructure of the magnet contains (Zr) x Ti y V1 phase and (Zr) a Ti b Phase B2; Where x = 4~8, y = 2~4, a = 2~4, b = 1~2; (Zr) x Ti y The V1 phase is distributed at the triangular grain boundary junctions; (Zr) a Tib The B2 phase is needle-like and extends through the Nd-rich phase; Rich Nd phase and (Zr x Ti y The volume ratio of V1 is (2.5~5.5):1; Rich Nd phase and (Zr a Ti b The volume ratio of phase B2 is (7.5~15):1.
[0011] As a further improvement of the present invention, Nd-rich phase and Zr x Ti y The volume ratio of the V1 phase is (3.0~4.5):1; the Nd-rich phase and (Zr) a Ti b The volume ratio of phase B2 is (9~12):1.
[0012] A method for preparing an RTB sintered NdFeB magnet, comprising the following steps performed in sequence: melting, hydrogen crushing, powdering, forming, isostatic pressing, sintering, primary aging treatment and secondary aging treatment; The melting process employs a rapid solidification sheet process, with a melting temperature of 1450℃~1490℃, resulting in a casting sheet thickness of 0.10 mm~0.60 mm. The hydrogen crushing process includes a hydrogen absorption process and a hydrogen dehydrogenation process. The hydrogen absorption time is 1 h to 3 h and the hydrogen absorption temperature is 20℃ to 300℃. The hydrogen dehydrogenation time is 3 h to 7 h and the hydrogen dehydrogenation temperature is 550℃ to 600℃. A lubricant is added during the powdering process, and the amount of lubricant added is 0.02% to 0.1% of the mass of the mixed fine powder. The molding process is carried out under a magnetic field strength of 1.3 T to 2.5 T. The sintering temperature is 1000℃~1200℃, the sintering time is 5 h~15 h, and the sintering vacuum degree is ≤0.02 Pa.
[0013] As a further improvement of the present invention, the particle size of the powder obtained by the powder preparation is 2.5μm~6.0μm.
[0014] As a further improvement of the present invention, the temperature of the first-stage aging treatment is 800℃~950℃ and the time is 2.5 h~5.5 h; the temperature of the second-stage aging treatment is 430℃~530℃ and the time is 2.5 h~6.0 h.
[0015] As a further improvement of the present invention, after the secondary aging treatment, a grain boundary diffusion treatment step is also included; Before the grain boundary diffusion treatment, the magnet is made into a sheet with a thickness of 2.0 mm to 10.0 mm; The grain boundary diffusion treatment includes primary diffusion and secondary diffusion; The temperature for the first-stage diffusion is 800℃~950℃, and the time is 8h~20h; The secondary diffusion is carried out at a temperature of 430℃~530℃ for a time of 6 h~20 h. The grain boundary diffusion treatment involves adding a heavy rare earth diffusion source, which is a Tb alloy and / or a Dy alloy, and the amount added accounts for 0 to 1.0 wt% of the magnet mass.
[0016] In this invention, the performance of the matrix magnet is improved by the interaction and coupling relationship between trace elements, the combination of trace elements and boron elements in the main phase, and the formation of a new phase in the triangular region connecting the Nd-rich phase and the main phase. Moreover, the coercivity is improved by the diffusion of grain boundaries, thereby obtaining a magnet with high remanence and high coercivity. Attached Figure Description
[0017] For ease of explanation, the present invention will be described in detail below with reference to the preferred embodiments and accompanying drawings.
[0018] Figure 1 The raw material formulation tables for each embodiment and comparative example are shown in the figure. Figure 2 Tables showing the detection of magnetic properties of the matrix and grain boundaries after diffusion in each embodiment and comparative example; Figure 3 The matrix and grain boundary diffusion phase analysis and volume percentages of each embodiment and comparative example are shown. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0021] like Figures 1 to 3 As shown, an RTB sintered NdFeB magnet of the present invention comprises the following components by total mass: R: greater than or equal to 29.5 wt%, wherein R is a rare earth element, and wherein R contains at least Nd; Cu: 0.25wt%~0.60wt%; Ga: 0.15wt%~0.45wt%; B: 0.96wt%~1.20wt%; Fe: 57.0wt%~67.0wt%; Total amount of Zr, Ti and V: 0.20wt%~0.85wt%; The ratio of the total mass of Zr and Ti to the mass of V is (0.4~6):1; The ratio of the mass of B to the total mass of Zr and Ti is (1.6~12):1.
[0022] In this invention, the total amount of Zr, Ti and V is 0.30 wt% to 0.55 wt%; the ratio of the total mass of Zr and Ti to the mass of V is (1.5 to 4):1; wherein, the content of Zr is 0.05 wt% to 0.35 wt%; the content of Ti is 0.05 wt% to 0.25 wt%; and the content of V is 0.10 wt% to 0.25 wt%.
[0023] In this invention, the content of B is 0.98 wt%~1.10 wt%; the mass ratio of B to the total mass of Zr and Ti is (2~8):1; the content of Cu is 0.35 wt%~0.55 wt%; the content of Fe is 60.0 wt%~65.0 wt%; the magnet also contains Co, and the content of Co is ≤1.5 wt%.
[0024] Specifically, the present invention comprises the following components: R≥29.5%, where R represents rare earth elements, including Nd; Cu: 0.25wt%-0.60wt%; Ga: 0.15wt%-0.45wt%; B: 0.96wt%-1.20wt%; Fe: 57.0%-67.0wt%; Zr+Ti+V: 0.20 wt%-0.85 wt%, Zr+T to V mass ratio is (0.4~6):1; B to Zr+Ti mass ratio is (1.6~12):1; In this invention, the content of R is 29.5%-32.5wt%, such as 30.5wt%, 31.0wt%, and 32.0wt%; the type of R includes Pr or RH, where RH is a heavy rare earth element. In this invention, the Nd content is 20.0%-26.0wt%, for example 22.5wt%, 23.0wt%, 23.5wt%.
[0025] In this invention, the RH content is ≤3.0wt%, for example, 0wt%, 0.5wt%, or 1.0wt%.
[0026] In this invention, the content of Zr+Ti+V is 0.20%-0.85 wt%, for example, 0.30 wt%, 0.45 wt%, or 0.60 wt%; the mass ratio of Zr+Ti to V is (0.4-6):1, for example, 1.5:1, 2.0:1, or 3.0:1; wherein, Zr+Ti+V refers to the sum of the mass content of Zr, Ti, and V in the R TB magnet, with Zr content of 0.05-0.35 wt%, for example, 0.10 wt%, 0.15 wt%, or 0.20 wt%; Ti content of 0.05-0.25 wt%, for example, 0.10 wt%, 0.15 wt%, or 0.20 wt%; and V content of 0.10-0.25 wt%, for example, 0.10 wt%, 0.15 wt%, or 0.20 wt%.
[0027] In this invention, the mass ratio of B to Zr+Ti is (1.6~12), for example, 2:1, 4:1, 6:1.
[0028] In this invention, the RTB magnet may also contain conventional additive elements in the art, such as Al and Co; In this invention, the content of R is 29.5wt%~32.5wt%, the content of Nd is 20.0wt%~26.0wt%, and R also includes Pr and / or heavy rare earth element RH, where RH is Tb and / or Dy, and the content of RH is ≤3.0 wt%.
[0029] In this invention, the interaction and coupling relationships between trace elements, the pairing of trace elements with the main phase boron element, and the new phase formed by the triangular region connecting the Nd-rich phase and the main phase are used to prepare RTB sintered NdFeB magnets. In-depth analysis reveals a new (Zr) phase that inhibits grain growth and optimizes the grain boundary structure. x Ti y The V1 phase, in which x is 4~8 and y is 2-4, improves its performance and the permeability of grain boundary diffusion.
[0030] Within this invention, the microstructure of the magnet contains (Zr) x Ti y V1 phase and (Zr) a Ti b Phase B2; Where x = 4~8, y = 2~4, a = 2~4, b = 1~2; (Zr) x Ti y The V1 phase is distributed at the triangular grain boundary junctions; (Zr) a Ti b The B2 phase is needle-like and extends through the Nd-rich phase; Rich Nd phase and (Zr x Ti y The volume ratio of V1 is (2.5~5.5):1; Rich Nd phase and (Zr a Ti b The volume ratio of phase B2 is (7.5~15):1; Rich Nd phase and Zr x Ti y The volume ratio of the V1 phase is (3.0~4.5):1; the Nd-rich phase and (Zr) a Ti b The volume ratio of phase B2 is (9~12):1.
[0031] Specifically, (Zr x Ti y The V1 phase is located at the triangular grain boundary junction (between the main phase and the Nd-rich phase); the Nd-rich phase and (Zr) x Ti y The volume ratio of the V1 phase is (2.5~5.5):1, such as 3:1, 4:1, 5:1. The phase and volume ratio can be analyzed using an EPMA electron probe microanalyzer and an XRD diffractometer. In this invention, (Zr) a Ti b Phase B2 is located throughout the Nd-rich phase distribution, where the Nd-rich phase and (Zr) a Ti b The volume ratio of the B2 phase is (7.5~15):1, such as 8:1, 9:1, 10:1. The phase and volume ratio can be analyzed using EPMA electron probe microanalysis equipment and XRD diffractometer. In this invention, the main phase of RTB sintered NdFeB is connected by (Zr) at the triangular grain boundaries. x Ti y The V1 phase and the Nd-rich phase at the grain boundaries surround and encapsulate the magnet, strengthening its shell structure and improving its performance. The (ZraTib)B2 phase is located throughout the Nd-rich phase distribution, mainly exhibiting a needle-like distribution. It consumes boron and promotes the distribution and formation of the Nd-rich phase, thereby enhancing the magnet's coercivity.
[0032] The present invention also provides a method for preparing RTB sintered NdFeB magnets, comprising the following steps performed in sequence: melting, hydrogen crushing, powdering, forming, isostatic pressing, sintering, primary aging treatment and secondary aging treatment; The smelting process employs a rapid solidification sheet process, with a smelting temperature of 1450℃~1490℃, resulting in a sheet thickness of 0.10mm~0.60mm. The hydrogen crushing process includes a hydrogen absorption process and a hydrogen removal process. The hydrogen absorption time is 1 h to 3 h and the hydrogen absorption temperature is 20℃ to 300℃. The hydrogen removal time is 3 h to 7 h and the hydrogen removal temperature is 550℃ to 600℃. A lubricant is added during the powdering process, wherein the amount of lubricant added is 0.02% to 0.1% of the mass of the mixed fine powder; The molding process was carried out under a magnetic field strength of 1.3 T to 2.5 T. The sintering temperature is 1000℃~1200℃, the sintering time is 5 h~15 h, and the sintering vacuum degree is ≤0.02 Pa.
[0033] The particle size of the powder obtained from the grinding process is 2.5μm to 6.0μm, preferably 3.0 to 4.5μm.
[0034] In this invention, the temperature of the first-stage aging treatment is 800℃~950℃ and the time is 2.5 h~5.5 h; the temperature of the second-stage aging treatment is 430℃~530℃ and the time is 2.5 h~6.0 h.
[0035] In this invention, after the secondary aging treatment, a grain boundary diffusion treatment step is also included; Before grain boundary diffusion treatment, the magnet is made into a sheet with a thickness of 2.0 mm to 10.0 mm; Grain boundary diffusion treatment includes primary diffusion and secondary diffusion; The temperature for first-order diffusion is 800℃~950℃, and the time is 8h~20h; The temperature for secondary diffusion is 430℃~530℃, and the time is 6 h~20 h; A heavy rare earth diffusion source is added during the grain boundary diffusion treatment. The heavy rare earth diffusion source is a Tb alloy and / or a Dy alloy, and its addition amount accounts for 0~1.0 wt% of the magnet mass.
[0036] Specifically, the melting temperature for the rapid solidification sheet process is 1450~1490℃, for example, 1460℃; the sheet thickness is 0.10~0.60mm, for example, 0.25um; during hydrogen decomposition, the hydrogen absorption time is 1~3h, and the hydrogen absorption temperature is 20~300℃; the dehydrogenation time is 3~7h, and the dehydrogenation temperature is 550~600℃, for example, 580℃; a lubricant needs to be added during powder preparation, and the lubricant accounts for 0.02%~0.1% of the mass of the mixed fine powder, for example, 0.08%; the magnetic field strength for forming is 1. The sintering temperature is 1000-1200℃; the sintering time is 5-15h; the vacuum degree of sintering is ≤0.02Pa; the temperature range of the first-stage aging treatment is 800-950℃, for example 890℃; the treatment time of the first-stage aging treatment is 2.5-5.5h, for example 3.0h; the temperature range of the second-stage aging treatment is 430-530℃, with a more favorable range of 450-510℃; the treatment time of the second-stage aging treatment is 2.5-6.0h, for example 4.0h; In this invention, the particle size of the powder is 2.5-6.0 μm, for example 3.2 μm.
[0037] This invention also includes grain boundary diffusion treatment; the thickness of the magnetic sheet for grain boundary diffusion is 2.0 mm-10.0 mm; the first-stage temperature for grain boundary diffusion is 800-950℃, for example, 850℃; the first-stage aging time for grain boundary diffusion is 8-20 h, for example, 10 h; the second-stage temperature for grain boundary diffusion is 430-530℃, for example, 480℃; the second-stage aging time for grain boundary diffusion is 6-20 h, for example, 10 h; a heavy rare earth diffusion source is added during the grain boundary diffusion process, the type of heavy rare earth diffusion source is Tb alloy or Dy alloy, and the mass percentage of the heavy rare earth diffusion source is 0%-1.0 wt%, for example, 0.60 wt%.
[0038] The present invention provides the following embodiments and comparative examples, as detailed below: like Figure 1 As shown, Example 1 is carried out according to Figure 1The ingredients were formulated and then processed through melting, hydrogen crushing, powdering, molding, isostatic pressing, and sintering aging to obtain a blank. The blank was then subjected to magnetic property testing. Five-mm thick sheet magnets were sliced and subjected to grain boundary diffusion treatment to obtain the final magnet performance. The resulting mixture was melted in a vacuum induction melting furnace, and the molten metal was cast at 1460℃ and cooled on copper rollers at 40 rpm to obtain NdFeB alloy castings with an average thickness of 0.30mm. The castings were then subjected to hydrogen crushing, with a hydrogen absorption time of 1 hour, a dehydrogenation time of 5 hours, a dehydrogenation temperature of 600℃, and a cooling time of 2 hours. The powder was then subjected to an air jet mill with 0.08 wt% lubricant added. Powder with a particle size of 3.4 micrometers was obtained; the powder was magnetically oriented and shaped in a sealed oxygen-free glove box under a magnetic field of 1.7T; the green body was isostatically pressed at 200 MPa to obtain a magnet blank; the magnet blank was sintered at 1070℃ for 6 hours, then aged at 910℃ for 2 hours, and finally aged at 525℃ for 5 hours to obtain a neodymium iron boron magnet; the neodymium iron boron magnet was oriented and cut into 5.0 mm slices, and a layer of heavy rare earth Tb diffusion source (mass ratio 0.6 wt%) was coated on the magnet surface, and grain boundary diffusion was performed at 880℃ for 8 hours, followed by aging at 500℃ for 10 hours.
[0039] The RTB sintered NdFeB magnet formulations of Examples 2-10 and Comparative Examples 1-10 are designed as follows: Figure 1 The ingredients were prepared as described in Example 1, and all other preparation processes were the same. However, the amount of heavy rare earth element Tb used in Comparative Examples 9 and 10 differed from that in Comparative Examples 1-8. For details, please refer to [link to relevant documentation]. Figure 1 As shown, Figure 1 The symbol / indicates that the element is not present, and GBD represents grain boundary diffusion. In addition, C, O, Mn, etc. are inevitably introduced during the preparation of the RTB magnet of the product. The percentage content of these impurities recorded in the various examples and comparative examples does not include these impurities.
[0040] Within this invention, regarding magnetic performance testing, the remanence Br and intrinsic coercivity Hcj of the RTB magnets in Examples 1-10 and Comparative Examples 1-10 were obtained using the NIM test BH curves conducted by the National Institute of Metrology of China. Magnetic performance testing mainly includes the magnetic performance testing of the sintered blank and the magnetic performance testing of the sheet magnets after grain boundary diffusion. Specific magnetic performance testing of each matrix and after grain boundary diffusion is as follows: Figure 2 As shown.
[0041] Within this invention, based on the analysis of microstructure and phase structure, the plate-like magnets of Examples 1-10 and Comparative Examples 1-10 after grain boundary diffusion were analyzed using EPMA electron probe microanalysis and XRD (X-ray diffraction) to determine the distribution of Zr, Ti, and V elements in the RTB magnets, and quantitatively analyzed (Zr... x Ti y The content of the V1 phase was determined, with x ranging from 4 to 8 and y from 2 to 4. The distributions of Zr, Ti, and B elements were simultaneously determined, and quantitative analysis was performed (Zr...). a Ti b The content of phase B2 (a) was 2-4, and (b) was 1-2; quantitative analysis determined the content of Zr in RTB. x Ti y V1 phase, (Zr a Ti b The volume ratio of B2 phase to Nd-rich phase, Figure 3 These are the analytical results of Examples 1-10 and Comparative Examples 1-10. Figure 3 The symbol / indicates that the phase is not present.
[0042] Within this invention, through comparison, it is evident that the combined addition of Zr and Ti trace elements in Examples 1-2 and Comparative Examples 1-2 demonstrates that the effect of adding Zr and Ti is superior to adding them individually. The magnetic properties of the RTB sintered NdFeB blank magnets after the addition are superior, with a coercivity improvement of 0.4 kOe. Simultaneously, the coercivity improvement after grain boundary diffusion is superior, with a coercivity increment of 0.80-0.90 kOe. The volume ratio of the Nd-rich phase to the (Zr5Ti2)V1 phase is (4.5-4.8):1, and the volume ratio of the Nd-rich phase to the (Zr5Ti2)V1 phase is (12.1-12.6):1. Compared to the single addition, the main difference lies in the refinement of the grains by the (Zr5Ti2)V1 phase at the triangular grain boundaries and the needle-like (Zr2Ti)B2 grains penetrating the Nd-rich phase. This strengthens the shell structure of the triangular grain boundaries, optimizes the continuity of the Nd-rich phase and the grain boundary structure, thereby achieving the effect of improving coercivity.
[0043] Within this invention, Examples 4-5 and Comparative Examples 4-5 demonstrate that the combined addition of Zr and Ti within a certain range yields better results, with optimal effects achieved at amounts below or above the specified content. In Examples 4 and Comparative Example 4, when the amount added was too small, the resulting (Zr3Ti)V1 phase failed to effectively encapsulate the main phase grains at the triangular grain boundaries. The volume ratio of the Nd-rich phase to the (Zr3Ti)V1 phase was 7.2:1, thus failing to strengthen the shell structure between the main phase and the Nd-rich phase. The volume ratio of the Nd-rich phase to the (ZrTi)B2 phase, which is distributed needle-likely throughout the Nd-rich phase, was 16.8:1, which could not fully promote the formation and distribution of the Nd-rich phase and failed to achieve further flow of the Nd-rich phase. In this invention, in Example 5 and Comparative Example 5, the (Zr9Ti4)V1 phase formed after excessive addition agglomerates and enriches at the triangular grain boundaries, and the (Zr5Ti3)B2 phase formed through the Nd-rich phase does not exhibit needle-like shape, thus disrupting the continuous fluidity of the Nd-rich phase. Therefore, the blank performance of the RTB sintered NdFeB blank magnet is low, and the coercivity improvement after grain boundary diffusion is also low.
[0044] Within this invention, Examples 3, 6, and 7 and Comparative Examples 3, 6, and 7 illustrate that the addition and content of V element play a crucial role in the formulation design. In Examples 3 and Comparative Example 3, the RTB sintered NdFeB magnets without added V element did not form the (Zr7Ti3)V1 phase, the shell structure at the triangular grain boundaries was not strengthened, and the main phase grains were not encapsulated. Therefore, the coercivity of the RTB sintered NdFeB blank magnets was 0.4 kOe lower, and the increase in coercivity after grain boundary diffusion was also 1.2 kOe lower.
[0045] In this invention, in Example 6 and Comparative Example 6, the addition of a small amount of V resulted in the (Zr3Ti)V1 phase failing to effectively suppress abnormal grain growth at the triangular grain boundaries and failing to enhance the pinning effect of the antimagnetizing domain walls. The volume ratio of the Nd-rich phase to the (Zr3Ti)V1 phase was 7.5:1. The coercivity of the prepared RTB sintered NdFeB blank magnet was 0.6 kOe lower, and the increase in coercivity after grain boundary diffusion was also 1.0 kOe lower.
[0046] In this invention, in Example 7 and Comparative Example 7, the excessive addition of V resulted in the formation of an excessively thick non-magnetic phase layer of (Zr9Ti4)V1 phase at the grain boundaries, which isolated the main phase grains and weakened the magnetic exchange coupling between grains. The volume ratio of the Nd-rich phase to the (Zr3Ti)V1 phase was 2.2:1. The coercivity of the prepared RTB sintered NdFeB blank magnet was 0.4 kOe lower, and the increase in coercivity after grain boundary diffusion was also 1.6 kOe lower.
[0047] Within this invention, Example 8 and Comparative Example 8 illustrate that the (Zr5Ti2)B2 phase formed by Zr, Ti, and B elements failed to promote the formation and flow distribution of the Nd-rich phase. The volume ratio of the Nd-rich phase to the (Zr5Ti2)B2 phase was 6.4:1. The coercivity of the prepared RTB sintered NdFeB blank magnet was 0.4 kOe lower, and the increase in coercivity after grain boundary diffusion was also 1.3 kOe lower.
[0048] Within this invention, Examples 9-10 and Comparative Examples 9-10 demonstrate that the prepared RTB sintered NdFeB magnets exhibit superior grain boundary diffusion permeability. Increasing the grain boundary diffusion by 0.2 wt% of heavy rare earth diffusion sources still failed to achieve the desired magnetic properties.
[0049] Within this invention, (Zr) x Ti yThe V1 phase is located at the triangular grain boundary junction (between the main phase and the Nd-rich phase) and (Zr a Ti b The B2 phase is located throughout the Nd-rich phase distribution and mainly exhibits a needle-like distribution. It is key to improving the magnet's coercivity.
[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An RTB sintered NdFeB magnet, characterized in that, The total mass of all components includes the following components: R: greater than or equal to 29.5 wt%, wherein R is a rare earth element, and R contains at least Nd, wherein the Nd content is 20.0%~26.0 wt%; Cu: 0.25wt%~0.60wt%; Ga: 0.15wt%~0.45wt%; B: 0.96wt%~1.20wt%; Fe: 57.0wt%~67.0wt%; Total amount of Zr, Ti and V: 0.20wt%~0.85wt%; in, The ratio of the total mass of Zr and Ti to the mass of V is (0.4~6):1; The mass ratio of B to the total mass of Zr and Ti is (1.6~12):
1.
2. The RTB sintered NdFeB magnet according to claim 1, characterized in that, The content of R is 29.5 wt% to 32.5 wt%, and the content of Nd is 20.0 wt% to 26.0 wt%. The R also includes Pr and / or heavy rare earth element RH, wherein RH is Tb and / or Dy, and the content of RH is ≤3.0 wt%.
3. The RTB sintered NdFeB magnet according to claim 1, characterized in that, The total amount of Zr, Ti and V is 0.30wt%~0.55wt%; the mass ratio of the total mass of Zr and Ti to the mass of V is (1.5~4):1; The Zr content is 0.05 wt% ~ 0.35 wt%; the Ti content is 0.05 wt% ~ 0.25 wt%; and the V content is 0.10 wt% ~ 0.25 wt%.
4. The RTB sintered NdFeB magnet according to claim 1, characterized in that, The content of B is 0.98 wt% to 1.10 wt%; The ratio of the mass of B to the total mass of Zr and Ti is (2~8):1; The Cu content is 0.35 wt%~0.55 wt%; The Fe content is 60.0 wt%~65.0 wt%; The magnet also contains Co, and the Co content is ≤1.5wt%.
5. The RTB sintered NdFeB magnet according to claim 1, characterized in that, The microstructure of the magnet contains (Zr) x Ti y V1 phase and (Zr) a Ti b Phase B2; Where x = 4~8, y = 2~4, a = 2~4, b = 1~2; (Zr) x Ti y The V1 phase is distributed at the triangular grain boundary junctions; (Zr) a Ti b The B2 phase is needle-like and extends through the Nd-rich phase; Rich Nd phase and (Zr x Ti y The volume ratio of V1 is (2.5~5.5):1; Rich Nd phase and (Zr a Ti b The volume ratio of phase B2 is (7.5~15):
1.
6. The RTB sintered NdFeB magnet according to claim 5, characterized in that, Rich Nd phase and Zr x Ti y The volume ratio of the V1 phase is (3.0~4.5):1; the Nd-rich phase and (Zr) a Ti b The volume ratio of phase B2 is (9~12):
1.
7. A method for preparing an RTB sintered NdFeB magnet, characterized in that, The process includes the following steps performed in sequence: smelting, hydrogen crushing, powdering, forming, isostatic pressing, sintering, primary aging treatment and secondary aging treatment; The smelting process employs a rapid solidification sheet process, with a smelting temperature of 1450℃~1490℃, resulting in a casting sheet thickness of 0.10mm~0.60mm. The hydrogen crushing process includes a hydrogen absorption process and a hydrogen removal process. The hydrogen absorption time is 1 h to 3 h and the hydrogen absorption temperature is 20℃ to 300℃. The hydrogen removal time is 3 h to 7 h and the hydrogen removal temperature is 550℃ to 600℃. A lubricant is added during the powdering process, and the amount of lubricant added is 0.02% to 0.1% of the mass of the mixed fine powder. The molding process is carried out under a magnetic field strength of 1.3 T to 2.5 T. The sintering temperature is 1000℃~1200℃, the sintering time is 5 h~15 h, and the sintering vacuum degree is ≤0.02 Pa.
8. The preparation method according to claim 7, characterized in that, The particle size of the powder obtained by the powder preparation is 2.5μm~6.0μm.
9. The preparation method according to claim 7, characterized in that, The first-stage aging treatment is carried out at a temperature of 800℃~950℃ for 2.5 h~5.5 h; the second-stage aging treatment is carried out at a temperature of 430℃~530℃ for 2.5 h~6.0 h.
10. The preparation method according to claim 7, characterized in that, Following the secondary aging treatment, a grain boundary diffusion treatment step is also included; Before the grain boundary diffusion treatment, the magnet is made into a sheet with a thickness of 2.0 mm to 10.0 mm; The grain boundary diffusion treatment includes primary diffusion and secondary diffusion; The temperature for the first-stage diffusion is 800℃~950℃, and the time is 8h~20h; The secondary diffusion is carried out at a temperature of 430℃~530℃ for a time of 6 h~20 h. The grain boundary diffusion treatment involves adding a heavy rare earth diffusion source, which is a Tb alloy and / or a Dy alloy, and the amount added is 0 to 1.0 wt% of the magnet mass.